Preparing teachers to mentor beginning teachers: an Australian case study. Issue 3 (4th September 2017) - Beutel, Denise; Crosswell, Leanne; Willis, Jill; Spooner-Lane, Rebecca; Curtis, Elizabeth; Churchward, Peter
Abstract : Purpose: The purpose of this paper is twofold: first, to present an Australian mentor preparation program designed to prepare experienced teachers to mentor beginning teachers and second, to identify and discuss mentor teachers' personal and professional outcomes and the wider contextual implications emerging from the Mentoring Beginning Teachers (MBT) mentor preparation program. Design/methodology/approach: This case study, situated within Queensland, Australia, draws on qualitative data collected via interviews and focus groups with mentor teachers who participated in a large-scale systemic mentor preparation program. The program positions mentoring as supportive, based on a process of collaborative inquiry and encouraging critically reflexive praxis with the mentor professional learning focusing on reflection, dialog and criticality. Findings: Initial findings show the outcomes of the mentor preparation program include building a common language and shared understanding around the role of mentor, consolidating a collaborative inquiry approach to mentoring and providing opportunity for self-reflection and critique around mentoring approaches and practices. Some findings, such as a greater self-awareness and validation of mentors' own teaching performance, have confirmed previous research. However, the originality of this research lies in the personal and professional impacts for mentor teachers and the wider contextual impacts that have emerged from the study. Practical implications: The study highlights the impact of the mentor preparation program on the professional learning of teacher-mentors and contributes to the current lack of empirical research that identifies the personal and professional impacts for mentors and the wider contextual factors that impact effective mentoring in schools. Originality/value: The originality of this research lies in the personal and professional impacts for mentor teachers and the wider contextual impacts more broadly that have emerged from the study.